Local Knowledge and Adaptive Strategies of Farmers to Deal with Spodoptera Frugiperda in Corn: Pengetahuan Lokal Dan Strategi Adaptif Petani Menghadapi Spodoptera Frugiperda Pada Jagung - Yulia Oliviana Gaib (Agrifarm : Jurnal Ilmu Pertanian, 2025)
Spodoptera frugiperda (FAW) is the main threat to the early vegetative phase of corn in North Gorontalo. This research aims to develop a typology of adaptive strategies based on local knowledge, serving as the foundation for contextual and affordable PHT recommendations. The qualitative approach is employed through a combination of focused ethnography, Participatory Rural Appraisal (PRA), and Grounded Theory analysis. Data were collected in three sub-districts (Kwandang, Gentuma Raya, Atinggola) through 28 in-depth interviews, 7 FGDs, 5 PRA sessions, and 9 farm-walks with purposive snowball sampling. The results indicate the presence of a "practical threshold" used by farmers: checking 20 random plants/beds every 5–7 days and acting if ≥5 plants are symptomatic or damaged yields a score of 3–4. Thematic coding resulted in three adaptive strategies: preventive (simultaneous planting, garden cleanliness, intercrops/cover crops), reactive (ash/sand shoots treatment, selective spray), and integrative (simple monitoring → plant treatment → measurable spray with MOA rotation). The ranking matrix places simultaneous planting, observation-based spraying, and simple monitoring as the most effective strategies according to farmers. The main obstacles include the simultaneous planting, limited scouting personnel, high cash costs, and a lack of affordable monitoring equipment. The drivers are group leadership, regular meetings, and small demonstration plots. The research resulted in a 6-step protocol that was agreed upon at the group/overlay level and was well-received because it was simple. The findings emphasized the need to strengthen monitoring, simultaneous planting coordination, and information curation (WA kiosk extensions) so that adaptive practices develop into collective habits.